EFFECT OF SAQ TRAINING ON SELECTED PHYSICAL FITNESS VARIABLE ON BASKETBALL PLAYERS - Rani, Savita; Deol, Nishan Singh; Singh, Amrinder; Singh, Gagandeep (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Basketball is very fascinating modern game with fast and excitement action. Successful performance in basketball requires the physical fitness and precise skill to accomplish desired result. This study aimed to find out the effect of 6 week SAQ training on physical fitness variables of basketball players. For this purpose the researcher selected 20 male basketball players, age ranges between 21-25 years. Samples were selected at Punjabi university Patiala (Punjab). Random sampling technique was applied to select the sample. Physical fitness variables i.e. speed, agility and explosive strength were selected for this study. The SAQ training administered for 6 weeks by the investigator himself. At the start of the programme data was collected on the selected physical fitness variables on basketball players as the pre-test data and at the end of 6 weeks the post-test data was collected for the analysis purpose. During data collection period, the subjects were not allowed to participate in any training and competition. As the training session an advance, the intensity of load was increased by increasing repetition, duration and difficulty level of exercise. The Statistical Package for the Social Sciences (SPSS) version 21 was used for all analyses. The differences in the mean of each group (Pre Group & Post Group) for selected variable were tested for the significance of difference by applying paired samples t-test. For testing the hypotheses, the level of significance was set at 0.05. The results showed that there is a statistically significant (P > .05) difference found between all the physical fitness variables i.e. speed, agility and explosive strength.The result proved that after 6 weeks of SAQ training on basketball players improve the rate of speed, agility and explosive strength.